Polymerase chain reaction assay for the detection of Helicobacter pylori in gastric biopsy specimens: comparison with culture, rapid urease test, and histopathological tests. Issue 7 (July 1994) - Fabre, R; Sobhani, I; Laurent-Puig, P; Hedef, N; Yazigi, N; Vissuzaine, C; Rodde, I; Potet, F; Mignon, M; Etienne, J P
Abstract : Ulcer recurrence is probably related to residual Helicobacter pylori (H pylori). Histological examination and culture are considered to be the most specific tests. CLO test is a rapid but less specific test, which is usually used as an alternative test to culture. The aim of this study was to investigate the efficiency of a simplified polymerase chain reaction (PCR) assay as a procedure for the diagnosis of gastric H pylori infection of patients. Biopsy specimens were obtained from antral mucosa of 58 patients at endoscopy and submitted to four tests for detection of H pylori. The bacteria were found in 53%, 43%, 48%, and 50% of patients according to the results of PCR, CLO test, culture, and histological examination. Twenty three patients had both negative histology and negative culture and PCR was negative in all of these. Thirteen patients were not classified because only histology or culture was positive and 10 of these had a positive PCR test. When the diagnosis of H pylori was established by agreement with both histology and culture or three positive tests out of four, 29 patients were H pylori positive (28 having had three positive tests and one displaying positive histology and culture), and 26 were negative, and three undetermined. PCR proved the most sensitive and specific test. These results suggest the simplified PCR assay may be a valuable test for the detection of H pylori.